STUDI ETNOBOTANI SUKU DAYAK RIBUN DALAM PEMANFAATAN TUMBUHAN BERNILAI SENI DI DESA GUNAM KECAMATAN PARINDU KABUPATEN SANGGAU - Nggadas, Arit; Idham, M; Sisillia, Lolyta (Universitas Tanjungpura, 2019)
The Dayak Ribun Tribe Society has natural resources that can be developed as a source of community income. Interaction with nature still exists today so there is a need for research on the types of plants that are used, the art forms that are made and the parts of the plants that are used by the Dayak Ribun Tribe of Gunam Village, Parindu District, Sanggau District as art crafts. The method used in this study is a survey method with interview techniques for taking respondents to snowball sampling. Retrieval of data or information is carried out directly by researchers on selected respondents, prospective respondents are determined by respondents who have been interviewed beforehand and continue to the next respondent. Respondents were obtained as many as 32 people. Data collection is done by observation, in-depth interviews, and documentation using a camera. The number of plant species used in Gunam Village as raw material for crafts and raw materials for musical instruments as many as 14 species from 9 families includes Areaceae, Gleicheniaceae, Poaceae, Thymelaeaceae, Apocynaceae, Dipterocarpaceae, Simaroubaceae, Fagaceae and Moraceae. The part of the plant that was used by the community in Gunam Village was found as many as 9 types of stems, 2 types of leaves, 2 types of seeds, 1 root, 1 type of fruit and 1 bark. There were two types of plants that were used by more than one plant organs namely Kemenyan or Aquilaria sp and keraci or Lithocarpus sp. Art forms that are used in the form of crafts and musical instruments. Crafts include key chains, clothes racks, chairs, rings, bracelets, takin, mats, hats, necklaces, drinking glasses, plates, clothes, bags, ropes, while musical instruments are sapeKeywords: Dayak Ribun, Ethnobotany, Utilization of plant